Challenges in animal modelling of mesenchymal stromal cell therapy for inflammatory bowel disease - Chinnadurai, Raghavan (World J Gastroenterol, 2015)
Utilization of mesenchymal stromal cells (MSCs) for the treatment of Crohn’s disease and ulcerative colitis is of translational interest. Safety of MSC therapy has been well demonstrated in early phase clinical trials but efficacy in randomized clinical trials needs to be demonstrated. Understanding MSC mechanisms of action to reduce gut injury and inflammation is necessary to improve current ongoing and future clinical trials. However, two major hurdles impede the direct translation of data derived from animal experiments to the clinical situation: (1) limitations of the currently available animal models of colitis that reflect human inflammatory bowel diseases (IBD). The etiology and progression of human IBD are multifactorial and hence a challenge to mimic in animal models; and (2) Species specific differences in the functionality of MSCs derived from mice versus humans. MSCs derived from mice and humans are not identical in their mechanisms of action in suppressing inflammation. Thus, preclinical animal studies with murine derived MSCs cannot be considered as an exact replica of human MSC based clinical trials. In the present review, we discuss the therapeutic properties of MSCs in preclinical and clinical studies of IBD. We also discuss the challenges and approaches of using appropriate animal models of colitis, not only to study putative MSC therapeutic efficacy and their mechanisms of action, but also the suitability of translating findings derived from such studies to the clinic.